Long‐term loss to follow‐up in the TREAT Asia HIV Observational Database (TAHOD). Issue 7 (12th April 2019) - Jiamsakul, A; Kiertiburanakul, S; Ng, OT; Chaiwarith, R; Wong, W; Ditangco, R; Nguyen, KV; Avihingsanon, A; Pujari, S; Do, CD; Lee, M‐P; Ly, PS; et al.
Abstract : Objectives: With earlier antiretroviral therapy (ART) initiation, time spent in HIV care is expected to increase. We aimed to investigate loss to follow‐up (LTFU) in Asian patients who remained in care 5 years after ART initiation. Methods: Long‐term LTFU was defined as LTFU occurring after 5 years on ART. LTFU was defined as (1) patients not seen in the previous 12 months; and (2) patients not seen in the previous 6 months. Factors associated with LTFU were analysed using competing risk regression. Results: Under the 12‐month definition, the LTFU rate was 2.0 per 100 person‐years (PY) [95% confidence interval (CI) 1.8–2.2 among 4889 patients included in the study. LTFU was associated with age > 50 years [sub‐hazard ratio (SHR) 1.64; 95% CI 1.17–2.31] compared with 31–40 years, viral load ≥ 1000 copies/mL (SHR 1.86; 95% CI 1.16–2.97) compared with viral load < 1000 copies/mL, and hepatitis C coinfection (SHR 1.48; 95% CI 1.06–2.05). LTFU was less likely to occur in females, in individuals with higher CD4 counts, in those with self‐reported adherence ≥ 95%, and in those living in high‐income countries. The 6‐month LTFU definition produced an incidence rate of 3.2 per 100 PY (95% CI 2.9–3.4 and had similar associations but with greater risks of LTFU for ART initiation in later years (2006–2009: SHR 2.38; 95% CI 1.93–2.94; and 2010–2011: SHR 4.26; 95% CI 3.17–5.73) compared with 2003–2005. Conclusions: The long‐term LTFU rate in our cohort was low, with older age being associated with LTFU. The increased risk of LTFU with later years of ART initiation in the 6‐month analysis, but not the 12‐month analysis, implies that there was a possible move towards longer HIV clinic scheduling in Asia.